2023
DOI: 10.7759/cureus.33872
|View full text |Cite
|
Sign up to set email alerts
|

A Quality Assessment of Goals of Care Forms in a Sample of Older Patients in Various Care Settings in Quebec, Canada

Abstract: Objective: The objective of this study is to assess the completion and content of the Goals of Care (GOC) forms in three care settings in the province of Quebec, Canada.Methods: This is a retrospective, cross-sectional, mixed methods analysis of data extracted from the charts and GOC forms of patients aged over 65 who received services during the year 2018 in one of the three following care settings: (i) long-term care facility, (ii) acute care hospital, and (iii) home support services of a regional healthcare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…It appeared that the open-ended section was frequently used to add a second goal of care applicable in the event of health deterioration. This indicated that the GOC form could not capture the patient-centered nuances required regarding values and preferences in the event of severe illness [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…It appeared that the open-ended section was frequently used to add a second goal of care applicable in the event of health deterioration. This indicated that the GOC form could not capture the patient-centered nuances required regarding values and preferences in the event of severe illness [ 33 ].…”
Section: Discussionmentioning
confidence: 99%